TEAM TEACHING IN JAPAN FROM THE PERSPECTIVES OF THE ALTs, THE JTEs, AND THE STUDENTS - Andrea Ann Johannes (TEFLIN, 2012)
This case study explores team teaching in Japan from the perspectives of JTEs (Japanese English Teachers), ALTs (Assistant Language Teachers), and students. Special focus is attributed to teachers and studentsâ perceptions of ALT and JTE roles. To determine the perspectives of all three participants, 112 students, 4 JTES and 2 ALTs from a Japanese high school in Chiba Prefecture were surveyed. Fieldwork was conducted over a ten-day period at the research site in 2009 to collect data in the form of questionnaires, interviews, and class observations. The findings indicate more of a mismatch between studentsâ perceptions of their teachersâ roles than between teachers. The results also reveal the students prefer a combination of both teachers and find team-taught classes more beneficial to developing their English skills.